Suicide terrorists and terrorism : a suicidologist critically reviews the research - Lester, David, 1942- (Terrorism, hot spots and conflict-related issues, 2021)
"There has never been a thorough review of the research and speculation on suicide terrorism. I read roughly 600 articles on suicide terrorism for this book. 250 are cited because they had something to offer. 350 are listed separately as a reference source for others. There have been almost no experts on suicide writing on the topic. I found only three articles on suicide terrorism in suicidology or death journals. Those writing on suicide terrorism have little or no expertise in the field of suicidology. This review is written by a suicidologist. For example, writers on suicide terrorism never cite work on suicide in the oppressed, imitation and contagion effects in suicide, typologies of suicidal behavior, or mass murder. (The present author has written a book on mass murder and published research on mass murder in addition to his extensive work on suicide.) The book starts with introductory chapters on suicide and mass murder to provide a setting for the review. The book is a critical review and so will be provocative. All the speculations are mentioned, and the research is reviewed and, if appropriate, critiqued"--